The Impact of Implementing the Independent Curriculum on Improving Education Quality at SMPN 1 Labuhan Haji Barat, Aceh Selatan - Yulia (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study aims to analyze the impact of implementing the Independent Curriculum on improving educational quality at SMPN 1 Labuhan Haji Barat, Aceh Selatan. Using a qualitative research approach, data were collected through in-depth interviews, observations, and document analysis related to the curriculum implementation. The findings indicate that the implementation of the Independent Curriculum has a positive effect on students' engagement in the teaching and learning process, educators' creativity in designing lesson plans, and students' critical thinking skills. Additionally, there has been an increase in parental and community involvement in supporting educational activities at the school. This research recommends that the school continue to innovate and provide training for teachers to better understand and effectively implement the principles of the Independent Curriculum. The conclusion suggests that the implementation of the Independent Curriculum has the potential to enhance educational quality at SMPN 1 Labuhan Haji Barat and can serve as a model for other schools adopting similar curricula.